Augmented Latent Membrane Protein 1 Expression from Epstein-Barr Virus Episomes with Minimal Terminal Repeats - Repic, Allison M. (American Society for Microbiology (ASM), 2010)
The major oncogene of the Epstein-Barr virus (EBV), latent membrane protein 1 (LMP1), can be expressed from either of two promoters, ED-L1 or L1-TR, producing mRNAs of 2.8 kb or 3.5 kb, respectively. L1-TR, active in nasopharyngeal carcinoma and Hodgkin's lymphoma, is located within the first of a highly variable reiteration of terminal repeat (TR) sequences that are joined by random recombination upon circularization of the linear genome at entry into cells. To determine whether the resultant TR number affects LMP1 promoter activity, we isolated single-cell clones bearing episomes of distinct TR numbers (6TR to 12TR) from epithelial cells newly infected with EBV. LMP1 mRNA levels correlated directly with the quantity of LMP1 protein expressed but varied inversely to TR number. Unexpectedly, the 3.5-kb transcript predominated only at lower TR reiterations. Diminished L1-TR activity in the context of a higher TR count was confirmed with a green fluorescent protein (GFP) reporter construct driven by L1-TR. Various levels of LMP1, expressed from virus isogenic in all but TR number, produced divergent morphological and growth phenotypes in each cell clone. Abundant LMP1 in 6TR cells yielded a relatively cytostatic state compared to the proliferative one produced by intermediate and smaller amounts in 8TR and 12TR clones. These findings suggest that the diversification of TR number, inherent in a round of EBV reactivation and reinfection, may itself be a component of the oncogenic process. The replicative burst preceding onset of many EBV-linked cancers may increase the likelihood that LMP1 levels compatible with clonal outgrowth are achieved in a subset of infected cells.